Advanced strategies for screening and identifying RNA-targeted small molecules: Bridging therapeutic potential and innovation - Zukela Ruzi; Daxiong Han; Kailibinuer Aierken (Results in Chemistry)
The development of RNA-targeted small molecules has emerged as a promising and rapidly expanding field in drug discovery, offering new opportunities to address a wide range of diseases beyond protein-targeting therapies. RNA molecules, including messenger RNAs (mRNAs) and non-coding RNAs (ncRNAs), play fundamental roles in gene regulation, protein synthesis, and cellular stress responses. However, their dynamic nature and structural complexity have historically posed challenges in developing small molecules with high affinity and selectivity. In recent years, significant advancements in screening methodologies, such as high-throughput screening (HTS), small molecule microarrays (SMMs), and DNA-encoded libraries (DELs), have facilitated the identification of RNA-binding small molecules with enhanced specificity. Complementary approaches, including structure-based drug design (SBDD) and fragment-based drug discovery (FBDD), have provided critical insights into RNA-ligand interactions, enabling rational optimization of candidate molecules. The integration of emerging technologies, such as RNA sequencing and chemical crosslinking, has further enabled transcriptome-wide mapping of interactions and predictive modeling of binding affinity. This review presents a comprehensive analysis of the methodologies employed in the discovery of RNA-targeted small molecules, with a focus on their applications in bacterial riboswitches, viral RNA elements, and disease-associated RNAs, such as miRNA-21 and MALAT1. Despite recent progress, challenges remain, including the lack of well-defined RNA binding pockets and potential off-target effects. Strategies to overcome these obstacles are explored, highlighting the potential of RNA-targeted small molecules to address unmet therapeutic needs. By integrating cutting-edge technologies and multidisciplinary approaches, this review provides insights into current advances and future directions in RNA-targeted drug discovery.